Genome-Wide Analysis of the Musa WRKY Gene Family: Evolution and Differential Expression during Development and Stress - Goel, Ridhi; Pandey, Ashutosh; Trivedi, Prabodh K.; Asif, Mehar H. (Frontiers in Plant Science, 2016)
The WRKY gene family plays an important role in the development and stress responses in plants. As information is not available on the WRKY gene family in Musa species, genome-wide analysis has been carried out in this study using available genomic information from two species, Musa acuminata and Musa balbisiana. Analysis identified 147 and 132 members of the WRKY gene family in M. acuminata and M. balbisiana respectively. Evolutionary analysis suggests that the WRKY gene family expanded much before the speciation in both the species. Most of the orthologs retained in two species were from the γ duplication event which occurred prior to α and β genome-wide duplication (GWD) events. Analysis also suggests that subtle changes in nucleotide sequences during the course of evolution have led to the development of new motifs which might be involved in neo-functionalization of different WRKY members in two species. Expression and cis-regulatory motif analysis suggest possible involvement of Group II and Group III WRKY members during various stresses and growth/ development including fruit ripening process respectively.